Assessment of nurses’ knowledge on Basic Cardio Pulmonary Resuscitation (B-CPR) - Zacharopoulos, P.; Πρελορέντζου, Χ.; Merkouris, Anastasios (My University, 2007)
Aim: To assess the level of knowledge of the nursing staff on Basic Cardio-Pulmonary Resuscitation (B-CPR) according to the European Resuscitation Council guidelines (ERC 2000) and explore the correlation with demographic and other background factors. Material and method: The sample included 128 nurses and 107 assistant nurses from 13 hospitals in Attica and 3 hospitals in Crete. A questionnaire with 14 multiple choice questions which was developed for the specific purpose was used for data collection. Results: The results showed that nursing staff had a low level of knowledge on B-CPR (Mean.=5.88, SD=2.42). The vast majority of the participants (69.2%) did not know the exact rhythm of compression - ventilation. Only half of the sample (54,4%) has attended a Β-CPR seminar. Statistically significant differences were found for the geographical area, the type of department, the educational level, the participation in Β-CPR seminar and the time of the participation Conclusion: The results of this study showed the need for a systematic and continuous training on Β-CPR of all nurses, especially for the assistants and those who work in general departments.